Otak, Bahasa dan Pikiran dalam Mind Map - Siti Shalihah (Alfaz (Arabic Literatures for Academic Zealots), 2014)
Language and mind are firmly related to each other. The mind can not be separated from language, since language is expressions of minds. Without language, one can not be able to convey things in his/her minds and they are never be able to be understood by the others. Thus, language is the way to grasp one’s thought. This article deals with the relationship between Mind Map and the structure of brain, how it works, and what to do with language and thinking. From concept of mind map and how it works, it can be seen how it employs brain and even works by nature in line with it. In this way, Mind Map tries to optimize the functions of brain.